Big Data Analytics in Supply Chain Management: A Systematic Mapping Study - Souza, Thiago Vieira de; Farias, Kleinner; Bischoff, Vinicius (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2020)
In recent years, the capacity of big data analytics (BDA) has attracted the significant attention of researchers linked to academia and industry professionals. This capacity is related to the possibility of managing informations advanced to reach its supply chain. In other words, information technology uses integrated systems, which facilitates innovation and the diffusion of knowledge throughout this supply chain. However, researchers and professionals still need to explore the capacity potential of BDA, in order to improve supply chain operational decision-making skills. This work classifies the state-of-the-art literature that applied BDA to the supply chain management (SCM). A Systematic Mapping Study was elaborated based on literature guidelines. A total of 50 primary studies were selected through a filtering process from initially 5,437 studies. These primary studies were used to answer the six research questions. The result of the classification showed that 64% of the studies are related to supply-chain management; most of the studies carried out empirical research; and approximately 50% of the primary studies investigated models for optimization process. This research provides to academics and industry professionals the gaps and future challenges related to BDA for SCM.